Expression pattern and clinical significance of β-catenin gene and protein in patients with primary malignant and benign bone tumors - Narges Khademian; Alireza Mirzaei; Ameinh Hosseini; Leila Zare; Shima Nazem; Pegah Babaheidarian; Alireza Sheikhi; Zohreh Abdolvahabi; Mostafa Ibrahimi; Khodamorad Jamshidi; Mahtab Rahbar; Vahid Salimi; et al. (Scientific Reports, 2022)
Abstract This study is aimed to unravel the status of local and circulating β-catenin in different primary bone tumors and its relevance to tumor types, severity, and chemotherapy. The β-catenin mRNA expression level and the expression of the protein (intensity level) were evaluated in tumor tissue and peripheral blood mononuclear cells of 150 patients with different types of primary bone tumors (78 malignant and 72 benign tumors) using Real-Time PCR and immunohistochemistry. The β-catenin mRNA expression level and the expression of the protein were increased in bone tumors which was positively correlated with the tumor malignancy. Amongst osteosarcoma, Ewing's Sarcoma, chondrosarcoma, osteochondroma, Giant Cell Tumor, and exostosis tumors, the osteosarcoma, and Giant Cell Tumor groups showed the highest level of β-catenin expression. The β-catenin expression in malignant bone tumors was significantly correlated with tumor grade, size, metastasis, tumor recurrent, and the level of response to chemotherapy. A similar pattern of β-catenin gene expression and its association with tumor characteristics was detected in the patient's peripheral blood cells. The simultaneous increase in the expression of the β-catenin gene and protein in tumor tissue and in circulating blood cells and its relationship with tumor severity indicates the possible promoting role of β-catenin in primary bone tumor pathogenesis.